Mechanisms of Helicobacter pylori antibiotic resistance and molecular testing - Nishizawa, Toshihiro; Suzuki, Hidekazu (Frontiers in Molecular Biosciences, 2014)
Antibiotic resistance in Helicobacter pylori (H. pylori) is the main factor affecting the efficacy of current treatment methods against infection caused by this organism. The traditional culture methods for testing bacterial susceptibility to antibiotics are expensive and require 10 to 14 days. Since resistance to clarithromycin, fluoroquinolone, and tetracycline seems to be exclusively caused by specific mutations in a small region of the responsible gene, molecular methods offer an attractive alternative to the above-mentioned techniques. The technique of polymerase chain reaction (PCR) is an accurate and rapid method for the detection of mutations that confer antibiotic resistance. This review highlights the mechanisms of antibiotic resistance in H. pylori and the molecular methods for antibiotic susceptibility testing.